2020
DOI: 10.1002/jcsm.12651
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia: prevalence, associated factors, and the risk of mortality and disability in Japanese older adults

Abstract: Background There is limited evidence on sarcopenia in Asian populations. This study aimed to clarify the prevalence, associated factors, and the magnitude of association with mortality and incident disability for sarcopenia and combinations of its components among Japanese community‐dwelling older adults. Methods We conducted a 5.8 year prospective study of 1851 Japanese residents aged 65 years or older (50.5% women; mean age 72.0 ± 5.9) who participated in health check‐ups. Sarcopenia was defined according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
193
2
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 279 publications
(217 citation statements)
references
References 50 publications
11
193
2
11
Order By: Relevance
“…The prevalence of sarcopenia in our study population was 18.6% overall, 9.7% among men, and 22.5% among women. The prevalence of sarcopenia in older Asians using AWGS2019 criteria has ranged from 16.4 to 22.8% overall, 11.5 to 21.8% among men, and 16.7 to 23.1% among women [ 42 , 43 , 44 ]. The prevalence of men in the present study was lower than that of previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of sarcopenia in our study population was 18.6% overall, 9.7% among men, and 22.5% among women. The prevalence of sarcopenia in older Asians using AWGS2019 criteria has ranged from 16.4 to 22.8% overall, 11.5 to 21.8% among men, and 16.7 to 23.1% among women [ 42 , 43 , 44 ]. The prevalence of men in the present study was lower than that of previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…2021, 22, 10246 2 of 13 general health and is therefore one of the major determinants of a healthy life expectancy. A recent epidemiological study confirmed that sarcopenia is strongly associated with an increased risk of all-cause mortality and disability [1]. Since the population is rapidly aging globally, preventing sarcopenia is an important task for public health.…”
Section: Introductionmentioning
confidence: 97%
“…Interest in sarcopenia, the age-related loss of skeletal muscle mass and function, is growing considerably. A recent systematic review and meta-analysis reported that the prevalence of sarcopenia in community-dwelling older adults is 10% [ 1 , 2 , 3 ]. Sarcopenia is a disorder characterized by progressive and generalized loss of skeletal muscle mass and function, and it is associated with increased adverse outcomes such as physical disability, poor quality of life, and death [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%